2019
DOI: 10.1111/vru.12826
|View full text |Cite
|
Sign up to set email alerts
|

The left lateral projection is comparable to horizontal beam radiography for identifying experimental small volume pneumoperitoneum in the canine abdomen

Abstract: Nontraumatic spontaneous pneumoperitoneum suggests the presence of gastrointestinal perforation; early detection can be lifesaving. Horizontal beam projections have been reported to be more sensitive than standard radiographic views for detecting small volumes of free peritoneal gas. This prospective, experimental, analytical study compared both left lateral (LL) and ventrodorsal (VD) standard views to horizontal beam projections for detecting small volumes of artificially induced pneumoperitoneum in live dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The lateral view with a horizontally directed x‐ray beam has historically been suggested as the most sensitive view for detecting small volume pneumoperitoneum 27,28 . Recently, however, a study comparing horizontal beam radiography to standard left lateral projections found that evaluation of standard left lateral views were not significantly different from the lateral horizontal projection for all volumes of air tested 9 . Another study evaluating right lateral projections, left lateral horizontal beam and ventrodorsal projections found free gas was more likely to be detected on lateral computed radiography images than other projections 29 .…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The lateral view with a horizontally directed x‐ray beam has historically been suggested as the most sensitive view for detecting small volume pneumoperitoneum 27,28 . Recently, however, a study comparing horizontal beam radiography to standard left lateral projections found that evaluation of standard left lateral views were not significantly different from the lateral horizontal projection for all volumes of air tested 9 . Another study evaluating right lateral projections, left lateral horizontal beam and ventrodorsal projections found free gas was more likely to be detected on lateral computed radiography images than other projections 29 .…”
Section: Discussionmentioning
confidence: 96%
“…This does, however, raise the question if inexperience may lead to overdiagnosis of free gas in practice, and therefore unnecessary surgery. A recent paper also demonstrated that experience in radiology increased the odds of achieving an accurate response, although this was when examining patients with iatrogenic pneumoperitoneum 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations